2021
DOI: 10.18844/cjes.v16i1.5528
|View full text |Cite
|
Sign up to set email alerts
|

Resource based learning design thinking (RBLDT): A model to improve students’ creative thinking skills, concept gaining, and digital literacy

Abstract: This study aims to investigate the effect of Resource Based Learning Design Thinking (RBLDT) model to improve student's creative thinking skills, concept gaining, and digital literacy. It is a quasi-experimental study using pre-test and post-test nonequivalent control group design. Furthermore, it was conducted at several senior high schools in Ambon, such as Senior High School 1, 2, 12, and Senior High School Siwalima Ambon in the odd semester of the 2019/2020 academic year. From each school, three classes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
8
0
2
Order By: Relevance
“…Alexander, B., Becker, S. A., Cummins, M., & Giesinger, C. H. (2017) explained that the ability to discern credible from inaccurate resources is foundational to digital literacy. Rumahlatu et al (2021) mentioned that digital literacy could also empower the students' creative thinking. Digital Literacy helped the students succeeded in various fields, such as in learning (Sivrikaya, M. H., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Alexander, B., Becker, S. A., Cummins, M., & Giesinger, C. H. (2017) explained that the ability to discern credible from inaccurate resources is foundational to digital literacy. Rumahlatu et al (2021) mentioned that digital literacy could also empower the students' creative thinking. Digital Literacy helped the students succeeded in various fields, such as in learning (Sivrikaya, M. H., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is a life skill that encompasses not only the ability to use technological devices but also to socialise, have attitudes, think critically and creatively, and inspire others in their interpretation of information obtained through technological devices (Gruszczynska & Pountney, 2013). Therefore, digital literacy involves the ability to analyse, synthesise, and compare information from different sources as well as present, evaluate, and use the information ethically (Dominggus et al, 2021). In the era of globalisation, digital literacy has become one of the competencies that students must possess.…”
Section: Introductionmentioning
confidence: 99%
“…One of the effective ways to improve the quality of higher education for students is the transition to resource-based learning (RBL) in the process of cross-cultural training of future professionals in fitness and recreation. The issue of introduction of RBL students in the practice of the educational process of higher education is the subject of research of many Ukrainian and foreign scientists (Shu-Nu Chang, 2007; Nestulya et al, 2021;Rumahlatu et al, 2021). Generalizations of research on the issue of resource-based learning have revealed a large number of original interpretations of this concept.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, American scientists M. Hannafin and J. Hill under the term «RBL of students» understand the creation of a unique context for optimizing learning, combining tools for finding and interpreting information from different resources, consistent with the process of knowledge research and different educational models. Indonesian scientists D. Rumahlatu, K. Sangur note that «The RBL is one of the most important learning models used during this time, and it requires students to learn from a variety of sources to access and communicate using technology» (Krzystof, 2007;Rumahlatu et al, 2021). Ukrainian researchers interpret RBL as a dynamic process of organization and stimulation of independent cognitive activity of students on mastering the skills of active transformation of the information environment, which provides for the optimal use of the triad «student-teacher-librarian» of consolidated personnel, material and technical, educational and methodical, information and digital resources.…”
Section: Introductionmentioning
confidence: 99%